A Study of Health Status of Hotel and Restaurant Child Labor in Nepalgunj Sub-metropolitan - Acharya, Lalmani (Academia Research Journal, 2022)
The major aim of this research paper was to investigate the present health condition of child laborers who were working in the hotel and restaurants of Nepalgunj. Socio-economic condition and family background were analyzed to find out the health condition, of labour children. The study is mainly based on primary data collected form Nepalgunj Sub-metropolitan using purposive sampling techniques. 150 people in total responded to the survey. It is now widely acknowledged that child exploitation is a serious socioeconomic issue. Children are among the demographic groups that are most frequently neglected, abused, and subjected to the worst types of child labor. Child labor is a widespread occurrence in Nepal, both in terms of general employment and population. The child labor in hotel and restaurant is common in the urban areas of Nepal who are not getting proper health care and treatment. It is concluded from the study that child laborers in hotel and restaurant is one of the visible, exploitative and hazardous forms of child labour whose health condition is vulnerable. Poverty is one of the cause and consequence of child labour. It is linked to the socio-economic, political and cultural realities of the county. The adoption of new laws and policies only cannot prevent the child labour problem unless society as a whole is aware on child right issue.